Risk factors for delay in surgery for patients undergoing elective anterior cervical discectomy and fusion - Renfree, Sean P. (J Spine Surg, 2019)
BACKGROUND: Anterior cervical discectomy and fusion (ACDF) is well-tolerated by most patients and commonly necessitates only a short hospital admission. Surgical delay after hospital admission, however, may result in longer hospital stays, consequently increasing hospital resource utilization. The current study evaluates risk factors for surgical delay in patients undergoing elective ACDF. METHODS: A retrospective analysis of ACS-NSQIP data from 2006–2015 was performed. Patients undergoing elective ACDF were selected using current procedural terminology (CPT) codes (22251, 22252, 22554). A surgical delay was defined as surgery that occurred one day or later after initial hospital admission. Differences in outcomes between the non-delayed and delayed cohorts were evaluated with univariate analysis. Multivariate logistic regression was performed to identify risk factors for surgical delay. RESULTS: There were a total of 771 (2.0%) surgical delays out of 39,371 patients undergoing elective ACDF from 2006–2015. Multivariate analysis found partially dependent functional status (OR 5.88; 95% CI: 4.48–7.71; P<0.001), totally dependent functional status (OR 18.22; 95% CI: 9.60–34.59; P<0.001), ASA class 4 (OR 2.73; 95% CI: 1.70–4.38; P<0.001), bleeding disorders (OR 1.75; 95% CI: 1.08–2.85; P=0.024), male sex (OR 1.19; 95% CI: 1.03–1.38; P=0.019), and chronic steroid use (OR 1.76; 95% CI: 1.30–2.37; P<0.001) as independent predictors of delay. Univariate analysis found surgical delay was associated with a higher rate of post-operative major adverse events (4.8% vs. 1.1%; P<0.001), mortality (1.0% vs. 0.2%; P<0.001) and greater than five-fold increase in total length of stay (9.52 vs. 1.65 days; P<0.001). CONCLUSIONS: Impaired pre-operative functional status, a higher comorbidity burden, and chronic steroid use are risk factors for surgical delay, increased complications, and length of stay in patients undergoing elective ACDF. This is helpful information to consider given a rising incidence of cervical fusions in the Medicare population, a wide variation in costs, and increasing popularity of bundled-payment models. LEVEL OF EVIDENCE: 3.